KOMPETENSI KEPRIBADIAN GURU DAN MOTIVASI BELAJAR SISWA (STUDI KORELASI PADA MATA PELAJARAN PAI) - Huda, Mualimul (LP2M IAIN kUDUS, 2017)
Teachers have a great responsibility towards the continuity of the learning process in school. Be aware or not, in addition to the tools and all things related to the teaching and success of educational goals, it turns out the personality of teachers is a very decisive success of learning. To avoid apathy and students' forced obedience, the teacher should improve his personality competence, how a teacher can be a student learning partner, featuring a good personality that can serve as a role model for her students and become a driving force in learning. This research is a research with quantitative approach. The population of this study are all students of class VII SMPN 7 Kediri amounted to 317 students. While the sample in this study as many as 175 students. Sampling is determined by Random sampling technique. Data collection uses questionnaire and documentation method. While statistical data analysis uses product moment correlation formula. Based on the research results, it is obtained a conclusion that the personality competence of PAI teachers included in good category. Based on the results of correlation calculations, it can be deduced that there is a strong and significant correlation between the teacher's personality competence to student learning motivation. The magnitude of the correlation coefficient is 0.616, while the correlation significance results obtained the value of t count = 10.2858. The value is greater than t table = 1.654 at the error rate of 5%. While the determination coefficient test obtained results 0.3794.